Effect of stroke rate on rowing technique - Kleshnev, V. (BioRow, 2021)
Stroke rate is an incredibly important factor of rowing technique, and every time we have discussed biomechanical variables and indicators, we mentioned their dependence on the stroke rate. Previously this topic was scattered around many publications, but here it is summarised in one place to give a clearer and more solid picture